Thermal performance of a closed-loop pulsating heat pipe with multiple heat sources - Kammuang-Lue N. (2014)
A closed-loop pulsating heat pipe with multiple heat sources (CLPHP w/MHS) was invented to be used as a heat transfer medium between a number of heat sources to a single heat sink. However, an issue on the suitable heat source arrangement that causes the heat pipe to have the highest thermal performance was suspicious. The CLPHP w/MHS was made of a copper capillary tube with 32 turns. There were three heat sources with nonidentical input heat flux installed along a longitudinal axis in the evaporator section. Experimental investigations were conducted by permuting the heat sources into six unduplicated arrangements. For the vertical CLPHPs, the highest thermal performance is achieved when heat sources are arranged in consecutive order ascending from the lowest heat flux at the inlet of the evaporator section, since working fluid is promoted to circulate in complete one direction and then the heat can transfer more continuously. Finally, for the horizontal CLPHPs, the highest thermal performance is achieved when the heat sources are arranged in opposite order to the case of vertical CLPHPs, that is, descending from the highest heat flux, since working fluid pulsates with no intermission stop and this causes the heat transfer to be not interrupted. © 2014 Copyright Taylor and Francis Group, LLC.